Contributions on the mechanisms of deformation in the sedimentary rocks of the Cachíos Formation, Yura, Arequipa region - Vivanco Leguia, Rosa Liliana (2023)
The Cachíos Formation of the Arequipa Sedimentary Basin is the most distinguishable lithostratigraphic unit of the Yura Group, due to its lithological attributes and its unusual deformational features. The Cachíos Fm. (± 603 m thick) is composed of interlayered very fine-grained siltstones and claystones, both dark gray to very dark gray. These sediments represent the Fl facies (cf. Miall 1985). It is common to find some intercalations of thin strata (<0.5 m) of gray-green quartz sandstones, and eventual thicker strata (up to ca. 12 m) of the same lithological material deformed as olistoliths. Such structures are frequently found with flexures, eventual folds, slumps, and normal non-sedimentary faults, and eventual siliciclastic dikes, which reflect a continuous process of deformation. Such facies association is representative for the Cachíos Fm., and it is due to its lithological attributes. This research aims to report in detail the mapping of facies related to such deformations, refine the real stratigraphic thickness, and better explain the geodynamics during the Callovian in this part of the Arequipa Basin.